Water Management Modelling in the Simulation of Water Systems in Coastal Communities - Sara, Barghi (Université d'Ottawa / University of Ottawa, 2013)
It is no longer a question of scientific debate that research declares our climate is changing. One of the most important and visible impacts of this phenomenon is sea level rise which has impacts on coastal cities and island communities. Sea level rise also magnifies storm surges which can have severely damaging impacts on different human made infrastructure facilities near the shorelines in coastal zones. In this research we are concerned about the proximity of water systems as one of the most vulnerable infrastructures in the coastal zones because of the impact of stormwater combining with sewage water. In Canada, the government has plans to address these issues, but to date, there needs to be further attention to stormwater management in coastal zones across the country. This research discusses the impacts of severe environmental events, e.g., hurricanes and storm surge, on the water systems of selected coastal communities in Canada. The purpose of this research is to model coastal zone water systems using the open source StormWater Management Modelling (SWMM) software in order to manage stormwater and system response to storms and storm surge on water treatment plants in these areas. Arichat on Isle Madame, Cape Breton, one of the most sensitive coastal zones in Canada, is the focal point case study for this research as part of the C-Change International Community-University Research Alliance (ICURA) 2009-2015 project.
Keywords: Climate change; Sea level rise; stormwater; water systems